KAPASITAS PERENCANAAN DESA DI KABUPATEN MUNA PROPINSI SULAWESI TENGGARA - Jopang Jopang; Zulfiah Larisu; Arifin Utha; Eko Harianto (Universitas Halu Oleo, 2018)
This study aims to analyze the capacity of village planning in Muna District. This study uses a qualitative approach by investigating village planning processes and outputs. The study locations are 7 seaside villages and 8 non-seas villages in Muna Regency. The scope of time is three budget years, namely 2015, 2016 and 2017.Procedure for collecting primary data through document studies. To obtain primary data, procedures for public consultation and focus group discussions were taken. A technical public consultation was agreed with the Community Empowerment Agency and Village Government of Muna Regency. Public consultation material was explored and developed from the results of focus group discussions. Focus group discussions were conducted at the village level, involving Village Devices, members of the Village Consultative Body, and Village Community Empowerment Institutions.The results of the study show that the capacity of village planning in Muna District is not yet optimal. The village planning system has not functioned properly in allocating and using inputs to produce planning output that is beneficial for achieving village development goals. Villages in Muna Regency have a planning document in the form of Village RPJM and Village RKP but in its arrangement are very formalistic, namely village planning norms are not administratively pursued in practice but can produce supporting documents required in legislation, while the social behaviour of the village plan compilers is not in line with the norms outlined in the Minister of Home Affairs Regulation No. 114 of 2014. Keywords: Capacity, Planning, Village